1984
DOI: 10.1002/jhet.5570210116
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐13 nuclear magnetic resonance spectra of phencyclidine analogs substituted in the piperidine and aromatic rings

Abstract: Natural abundance carbon‐13 chemical shifts are reported for the hydrochloride salts of phencyclidine (1a) and twelve analogs substituted in the piperidine and aromatic rings. The signals are assigned on the basis of chemical shift theory, SFORD multiplicities, signal intensities, and comparisons with related compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
3
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
6
3
0
Order By: Relevance
“…This was observed with 3-MeO-PCP and 3-Me-PCP and was consistent with that reported previously by Brine et al [20] where these shifts were also observed in the HCl salts of 4a-4c. One such effect included the observation of coalescence, e.g.…”
Section: Carbon Nuclear Magnetic Resonance Spectroscopysupporting
confidence: 93%
See 4 more Smart Citations
“…This was observed with 3-MeO-PCP and 3-Me-PCP and was consistent with that reported previously by Brine et al [20] where these shifts were also observed in the HCl salts of 4a-4c. One such effect included the observation of coalescence, e.g.…”
Section: Carbon Nuclear Magnetic Resonance Spectroscopysupporting
confidence: 93%
“…The impact of amine substitution on chemical shifts presented here were essentially consistent with those reported previously for unsubstituted PCP, PCPy and PCA hydrochlorides [20] and this was also observed by Iorio et al with related arylcyclohexylamine hydrochlorides and freebases. For example, a Δ b of 8.82 ppm was observed between the C 1' chemical shifts of 4-MeO-PCA (3b) and 4-MeO-PCP (4b) hydrochlorides and a 10.13 ppm Δ b between freebases.…”
Section: Carbon Nuclear Magnetic Resonance Spectroscopysupporting
confidence: 92%
See 3 more Smart Citations